2019
DOI: 10.1136/bmjopen-2018-023337
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic impact of post discharge bleeding post acute coronary syndrome within an outpatient setting: a systematic review

Abstract: ObjectiveThe primary objective was to determine the incidence of bleeding events post acute coronary syndrome (ACS) following hospital discharge. The secondary objective was to determine the prognostic impact of bleeding on mortality, major adverse cardiovascular events (MACE), myocardial re-infarction and rehospitalisation in the postdischarge setting.DesignA narrative systematic review.Data sourceMedline, Embase, Amed and Central (Cochrane) were searched up to August 2018.Study selectionFor the primary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…Previous studies have found that bleeding after ACS has an association with mortality similar to that of myocardial infarction 6 , and major bleeding correlates with a more prolonged mortality risk compared with ischemic events 7 . The incidence of post-discharge major bleeding within 1 year in patients with ACS has been reported as 1.3–5.6% in previous randomized trials (RCTs) and observational studies 8 10 , and up to one-third of patients discharged on dual antiplatelet therapy (DAPT) are reported to have had a bleeding complication within 12 months post-discharge 8 . Comparison of bleeding incidences among studies is difficult because of differences in the studied populations, follow-up times, in-hospital management, antithrombotic drugs used, and bleeding definitions 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that bleeding after ACS has an association with mortality similar to that of myocardial infarction 6 , and major bleeding correlates with a more prolonged mortality risk compared with ischemic events 7 . The incidence of post-discharge major bleeding within 1 year in patients with ACS has been reported as 1.3–5.6% in previous randomized trials (RCTs) and observational studies 8 10 , and up to one-third of patients discharged on dual antiplatelet therapy (DAPT) are reported to have had a bleeding complication within 12 months post-discharge 8 . Comparison of bleeding incidences among studies is difficult because of differences in the studied populations, follow-up times, in-hospital management, antithrombotic drugs used, and bleeding definitions 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…After hospital discharge, patients with ACS often remain on dual antiplatelet therapy for up to a year, and aspirin indefinitely, so their risk of bleeding complications persists in the longer term. 7 Major in-hospital bleeding has been associated with sociodemographic characteristics, cardiovascular and noncardiovascular comorbidities, and pharmacological and procedural characteristics, [8][9][10] leading to the development of risk scoring algorithms that stratify patients into risk profiles for these bleeding events. [8][9][10] However, it is unclear whether these characteristics are also predictive of bleeding events after hospital discharge.…”
mentioning
confidence: 99%
“…e. We have no data to estimate to which extent complications emerging in the course of treatment might have influenced the results of this study, though e.g. bleeding complications might have occurred in a non-negligible proportion of patients [50][51][52].…”
Section: Discussionmentioning
confidence: 94%